MPPT oscillations minimization in PV system by controlling non-linear dynamics in SEPIC DC-DC converter - M. Vaigundamoorthi; R. Ramesh; V. Vasan Prabhu; K. Arul Kumar (Institute of Advanced Engineering and Science, 2020)
Solar PV power generation has achieved rapid growth in developing countries which has many merits such as absence of noise, longer life, no pollution, less time for installation, and ease of grid interface. A maximum power point tracking circuit (MPPT) consists of DC-DC power electronics converters that are used to improve the energy attainment from solar PV array. This paper presents a detailed analysis to control of chaos, a non-linear dynamic in SEPIC DC-DC converter interfaced solar PV system, to minimize the oscillations near to MPP. In SEPIC DC-DC converter, the input inductor current is continuous and capable of sweeping the whole I-V curve of a PV module from open circuit voltage (Voc) to short circuit current (Isc) operating points. To trace the true maximum power point and to nullify the oscillations near to MPP, the yield output voltage needs to ensure period-1 operation.